Authorial style in the characterization of characters in the novel Laut Bercerita by Leila S Chudori - Wisnu Adwitia; Adyana Sunanda (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the authorial style employed by Leila Salikha Chudori in exploring and developing characters in the novel Laut Bercerita. The research adopted a qualitative descriptive design using a stylistic approach. Data were collected from narrative texts, dialogues, and symbolic expressions contained in the novel and analyzed through descriptive interpretation. The findings indicate that the author utilizes reflective narration, expressive language, meaningful dialogues, and symbolism to construct multidimensional characters with strong emotional and ideological qualities. The characterization of Biru Laut and Asmara Jati demonstrates psychological complexity, moral resilience, and emotional depth. In addition, the shifting narrative perspectives and poetic diction intensify readers’ emotional engagement and strengthen the representation of historical and social realities. The results also reveal that character development in the novel functions not only as a literary device but also as a medium for conveying educational values, including nationalism, empathy, and historical awareness. These values contribute to readers’ understanding of social justice and humanity. In conclusion, Chudori’s authorial style effectively integrates aesthetic and educational dimensions through character construction, making Laut Bercerita a relevant literary work for Indonesian language and literature learning, particularly at the secondary school level.